Increased Neutrophil Aging Contributes to T Cell Immune Suppression by PD-L1 and Arginase-1 in HIV-1 Treatment Naïve Patients - Liu, Kai; Huang, Hui-Huang; Yang, Tao; Jiao, Yan-Mei; Zhang, Chao; Song, Jin-Wen; Zhang, Ji-Yuan; Zhou, Chun-Bao; Yuan, Jin-Hong; Cao, Wen-Jing; Mu, Xiu-Ying; Zhou, Ming-Ju; et al. (Frontiers in Immunology, 2021)
Neutrophils are characterized by their heterogeneity. They fight against pathogens and are involved in tissue injury repair and immune system regulation. Neutrophils have an extremely short life span in the peripheral blood and undergo aging after being released from the bone marrow. The over-aggregation of aged neutrophils is associated with phenotypical and functional changes. Here, we aimed to investigate the dynamics of neutrophil aging and its relationship with T cell exhaustion in HIV-1 infection, as they are not well understood. In this study, we enrolled 23 treatment naïve (TN) patients, 23 individuals that had received antiretroviral therapy (ART), and 21 healthy controls (HC). In these cohorts, we measured the degree of neutrophil aging, and its possible correlation with T cell dysfunction. In TN patients, peripheral neutrophils showed a more distinct aging phenotype and were over-activated compared to those in ART-treated patients. The degree of neutrophil aging was positively correlated with HIV-1 RNA viral load and negatively correlated with CD4+ T cell count. Moreover, aged neutrophils had impaired reactive oxygen species (ROS) production after lipopolysaccharide (LPS) stimulation, and were characterized by increased PD-L1 and arginase-1 expression in a time-dependent manner. Aged neutrophils demonstrated an increased inhibition of IFN-γ and TNF-α secretion by CD8+ T cell compared to non-aged neutrophils. The inhibition effect could be partially reversed by blocking PD-L1 and arginase-1 in vitro, and LPS was identified as an important activator of neutrophil aging. These results provide evidence that dampening neutrophil aging may provide a novel approach to recover T cell dysfunction in patients with HIV-1 infection.